2021
DOI: 10.1177/08902070211010993
|View full text |Cite
|
Sign up to set email alerts
|

Dark, gray, or bright creativity? (Re)investigating the link between creativity and dishonesty

Abstract: The question of whether and, if so, how creativity and unethical behavior such as dishonesty are related to each other has been addressed in multiple studies, with mixed results overall. The aim of this Registered Report is to shed further light on this issue. We first present a meta-analysis on the relation between creativity and dishonesty comprising the samples from a pre-registered multi-lab study (on a different topic), which indicated no relation between the constructs in question ( k = 19, N = 2,154, rp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
(147 reference statements)
0
8
0
Order By: Relevance
“…In contrast, studies have also suggested that creativity and morality share a positive association (Shen, Yuan, Yi, Liu, & Zhan, 2019). Further, research has also indicated no/mixed relationships between the constructs, which is likely to be driven by the nature of creativity and dishonesty assessments (Ścigała, Schild, & Zettler, 2021).…”
mentioning
confidence: 99%
“…In contrast, studies have also suggested that creativity and morality share a positive association (Shen, Yuan, Yi, Liu, & Zhan, 2019). Further, research has also indicated no/mixed relationships between the constructs, which is likely to be driven by the nature of creativity and dishonesty assessments (Ścigała, Schild, & Zettler, 2021).…”
mentioning
confidence: 99%
“…Nonetheless, the relationship between creative thinking and academic dishonesty has not been extensively examined. The most influential line of research on the relation between creativity and unethical behavior suggests a positive relationship between the constructs ( Ścigała et al, 2021 ). Nevertheless, there is a common perception that people with a high level of creative thinking have a greater propensity for academic integrity.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Overall, our results are in line with those of earlier correlational studies, suggesting that the relation of creativity and unethical behaviour is not a simple one and depends on several contextual factors. For instance, prior research found a positive relation of subjective creativity and dishonest responses in the mind game, while the opposite relation was found for objective creativity [26]. Moreover, is has been shown that trait creativity is only linked to deviant behaviour in organizational settings for individuals low in moral identity [54] and another study only found a relation of dishonesty and trait creativity when participants were put in a creative state beforehand [40].…”
Section: Discussionmentioning
confidence: 99%